Analysis of Acceptance of Public Service Advertisements on News Coverage Impressions in Implementing 3M to Break the Chain of Transmission of Covid-19 - Riza Fatmawati; Didik Hariyanto (Universitas Muhammadiyah Sidoarjo, 2023)
Public Service Advertising is an advertisement that is non-profit and seeks to obtain social benefits in society. In public service advertisements, the aim is only to convey information so that people do positive things. Public Service Advertisement aired by Liputan 6 SCTV in Implementing 3 M to Break the Covid-19 Transmission Chain. This study has several indicators, namely Sender, Message, Channel and Receiver. This research was conducted on seven students of Communication Science, Muhhamadiyah University, Sidoarjo. This researcher uses a qualitative descriptive method. with data collection in the form of a Group Discussion Forum. In this study using the SMCR theory of David K. Berlo. The results that researchers can show that public service advertisements must be packaged in an attractive, simple, informative fact and actual. In a subject matter that occurs and is fundamental. Therefore, the addition of interesting animations and ideas can add a non-monotonous impression to public service advertisements. So in the process of receiving the message will respond to an information depending on each individual.